Construction of meaningful identities in the context of rheumatoid arthritis, motherhood and paid work: A meta‐ethnography. Issue 23 (4th September 2017) - Feddersen, Helle; Kristiansen, Tine Mechlenborg; Andersen, Pernille Tanggaard; Hørslev‐Petersen, Kim; Primdahl, Jette
Abstract : Aims and objectives: To derive new conceptual understanding about how women with rheumatoid arthritis manage their illness, motherhood and paid work, based on a comprehensive overview of existing knowledge, gained from qualitative studies. Background: Rheumatoid arthritis affects several social aspects of life; however, little is known about how women with rheumatoid arthritis simultaneously manage their illness, motherhood and paid work. Design: Qualitative metasynthesis. Methods: A qualitative metasynthesis informed by Noblit and Hare's meta‐ethnography was carried out, based on studies identified by a systematic search in nine databases. Results: Six studies were included. Social interactions in the performance of three interdependent subidentities emerged as an overarching category, with three subcategories: subidentities associated with (1) paid work, (2) motherhood and (3) rheumatoid arthritis. Pressure in managing one of the subidentities could restrict the fulfilment of the others. The subidentities were interpreted as being flexible, situational, contextual and competing. The women strove to construct meaningful subidentities by taking into account feedback obtained in social interactions. Conclusions: The subidentities associated with paid work and motherhood are competing subidentities. Paid work is given the highest priority, followed by motherhood and illness is the least attractive subidentity. Because of the fluctuating nature of the illness, the women constantly reconstruct the three interdependent subidentities. Relevance to clinical practice: When healthcare professionals meet a woman with rheumatoid arthritis, they should consider that she might not accept the subidentity as an ill person. Health professionals should not expect that women will prioritise their illness in their everyday life. This could be included in clinical conversation with the women.